2019
DOI: 10.1126/scitranslmed.aau3441
|View full text |Cite
|
Sign up to set email alerts
|

Targeting hepatic glucokinase to treat diabetes with TTP399, a hepatoselective glucokinase activator

Abstract: The therapeutic success of interventions targeting glucokinase (GK) activation for the treatment of type 2 diabetes has been limited by hypoglycemia, steatohepatitis, and loss of efficacy over time. The clinical characteristics of patients with GK-activating mutations or GK regulatory protein (GKRP) loss-of-function mutations suggest that a hepatoselective GK activator (GKA) that does not activate GK in β cells or affect the GK-GKRP interaction may reduce hyperglycemia in patients with type 2 diabetes while li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 48 publications
0
84
0
1
Order By: Relevance
“…unfortunately, the majority of the drugs that target GK activation for the treatment of T2dM have not been clinically successful due to side effects, such as hypoglycemia, steatohepatitis and loss of efficacy over time (8). However, TTP399, a hepato-elective GK activator, was assessed in a recently reported double-blind, 6-month study and it was found that TTP399 did not cause hypoglycemia and exhibited limited or no detrimental effect on plasma lipids or liver enzymes (34). Moreover, it is a liver specific GK activator without side effects of hypertension, highlighting the importance of liver selectivity when targeting GK activity (34).…”
Section: Metabolic Processing Of Glucose In the Liver Under Diabetic mentioning
confidence: 99%
“…unfortunately, the majority of the drugs that target GK activation for the treatment of T2dM have not been clinically successful due to side effects, such as hypoglycemia, steatohepatitis and loss of efficacy over time (8). However, TTP399, a hepato-elective GK activator, was assessed in a recently reported double-blind, 6-month study and it was found that TTP399 did not cause hypoglycemia and exhibited limited or no detrimental effect on plasma lipids or liver enzymes (34). Moreover, it is a liver specific GK activator without side effects of hypertension, highlighting the importance of liver selectivity when targeting GK activity (34).…”
Section: Metabolic Processing Of Glucose In the Liver Under Diabetic mentioning
confidence: 99%
“…Some agents like AZD6370, piragliatin, DS-7309, and ARRY-403 also terminated their drug development due to toxicity and loose of effectiveness with long-term administration. [47][48][49][50][51] Some examples of the GK activator presented in Table 3 with their stage of development and company.…”
Section: Dovepressmentioning
confidence: 99%
“…The study selection process is depicted in Figure 1 . Finally, seven independent, double-blind, randomized, controlled trials (a total of 762 patients) were included in the current meta-analysis 14,15,[19][20][21][22][23] . All the seven trials were of high quality with modified Jadad scores[?]…”
Section: Rct Selectionmentioning
confidence: 99%
“…The seven trials are multi-center clinical trials, among which 3 of them 14,19,21 are transnational multicenter trials. The category of GKA is different among the 7 trials, including MK-0941 14 , AZD1656 19 , LY2599506 20 , PF-04937319 21 , RO4389620 22 , HMS5552 23 , and TTP399 15 . In addition, all these 7 studies use identification of HbA1c as a criterion for patient inclusion, and the absence of glutamic acid decarboxylation antibody at admission is used to exclude patients with type 1 diabetes.…”
Section: Rct Selectionmentioning
confidence: 99%
See 1 more Smart Citation